Character Strengthening In The Development Of Islamic Religious Education Goals Of The 2013 Curriculum - Nur Syamsiah, Peni; Hamami, Tasman (AL-WIJDÃN Journal of Islamic Education Studies, 2022)
The disorder behavior of students is a challenging character problem that should be paid a lot of attention by education stakeholders in Indonesia. The character problem covers performance character such as not praying on time, being lazy to do assignments, and undisciplined and moral character like cheating on exams, disturbing friends, disrespecting each other, not listening to advice, and not respecting teachers and other character problems. Strengthening character in the development of the goals of Islamic religious education in the 2013 curriculum is a strategic solution to overcoming various character problems. The purpose of this study was to analyze and reveal character strengthening in the development of Islamic religious education goals in the 2013 curriculum. This research includes literature research, where the research uses descriptive analysis techniques to conclude systematically and factually from the object of thought. The results of this study explain that the development of the goals of character education in the Islamic religious education curriculum includes: integration between extracurricular activities such as reading prayers and reciting the Koran together and praying Duha on time, co-curricular activities including Hajj rituals and extracurricular activities such as scouts, paskibra, flash boarding schools and da'wah training.   Keywords: Character Strengthening, Islamic Religious Education (PAI), Curriculum 2013